Diagnostic flexible airway endoscopy in paediatric intensive care setting : an analysis of 109 examinations in HTAA, Kuantan - Asha'ari, Zamzil Amin; Yusof, Suhaimi; K.S, Sathananthar; Abdullah, Ahmad Fadzil (2013)
Objectives: Airway endoscopy is often the gold standard diagnostic tool in cases of infants and children with respiratory and voice problems. We analysed the flexible airway endoscopy performed in the paediatric intensive care unit of Hospital Tg Ampuan Afzan (HTAA), Kuantan, over a period of 6 years. Methods: Retrospective analysis of all the cases of flexible airway endoscopy performed in the paediatric ICU of HTAA from 2007 to 2012. All the procedures were done under topical anaesthesia, with or without intravenous sedation. The data were obtained from the medical charts, procedure charts and interview with the parents/guardian. Results: In this period, we performed 109 endoscopic investigations in 99 patients (aged 1 day-9 yrs) in the Paediatric ICU setting. Three different size flexible endoscopes were used to perform 97 laryngoscopic procedures and 12 bronchoscopic procedures. Repeat procedures were performed in 10 children. The most common indications for diagnostic endoscopy were stridor (76.1%), stertor (11%), chronic cough (5.5%), hoarseness (4.6%), and non-specific chest x-ray changes (2.8%). Laryngomalacia (71 cases) was the commonest diagnosis, which was the cause for 85.5% of stridor. Tracheobronchomalacia (9), subglottic stenosis (8) and obstructing adenoid tissue (4) were the next most common diagnoses. In addition, granulation tissue (3), vocal cord palsy (3), endobronchial foreign body (2), laryngeal tuberculosis (2), laryngeal hemangioma (1), laryngeal cleft (1), subglottic cyst(1) and pulmonary hemosiderosis(1) were other diagnosis found. Findings were normal in 3 (2.8%) cases. Diagnostic information was obtained in 94 of 99 patients. The diagnostic yield was highest in patients with stridor, and in patients with a tracheostomy. Minor complications occurred in altogether 4 cases; all were completely and rapidly reversible. Morbidity was minimal, and there was no death related to the procedure. Conclusions: Flexible fiberoptic bronchoscopy under sedation is a safe and valuable diagnostic tool for the management of infants and children with respiratory problems. The procedure can be done in the ICU setting for critically ill pediatric patients in whom evaluation of the airway in the operating room under general anesthesia would have been difficult.